2004
DOI: 10.1159/000079957
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Semi-Automated Technique of Cerebral Infarct Volume Measurement with CT

Abstract: Background: A reliable method of infarct volume measurement is needed if infarct volume is to be used as an outcome measure in clinical stroke trials. We investigated the reproducibility of a semi-automated method of computed tomography (CT) infarct volume measurement amongst three stroke research fellows with no formal neuroradiology training and two consultant neuroradiologists. Methods: CT brain scans for volumetric analysis were performed at 5 to 7 days in 34 patients with acute ischaemic stroke, of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Ischaemic stroke patients underwent a second CT brain scan at 5 to 7 days for determination of cerebral infarct volume, using a semi-automated technique [20]. Ankle brachial pressure index (ABPI) was used to classify degree of atherosclerosis where carotid duplex data were unavailable.…”
Section: Methodsmentioning
confidence: 99%
“…Ischaemic stroke patients underwent a second CT brain scan at 5 to 7 days for determination of cerebral infarct volume, using a semi-automated technique [20]. Ankle brachial pressure index (ABPI) was used to classify degree of atherosclerosis where carotid duplex data were unavailable.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma CRP and IL-6 were assayed using highsensitivity enzyme-linked immunosorbent assays described elsewhere [6]. Computed tomography (CT) brain scans were performed within 24 h to exclude primary intracerebral haemorrhage or stroke mimic and repeated at 5 to 7 days for volumetric analysis using a semi-automated technique [8]. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) score [9] at presentation and 5 to 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Until this occurs, PCT will not become incorporated into the routine clinical paradigm for the assessment of acute stroke patients for thrombolytic therapy. The need for better acute stroke diagnostics and training [22] has become greater since it was recently shown that the current technique of perfusion-diffusion mismatch is not sufficient for the selection of patients to be treated with thrombolysis [23]. …”
Section: Discussionmentioning
confidence: 99%